Taylor Morrow: capstone - Morrow, Taylor, artist (Colorado State University. Libraries, 2021)
The artist's statement: Art is derived from basic forms found in nature, crafted and stylized with our own complex perception of reality. Using simple lines of metal to form trees, creating large stone circles, or making wooden cubes allow the initial framework to be universally recognizable. Details such as the addition of paint, smaller wires, glossy beads, dynamically cut wood, or pools of liquid resin can be added to these basic, or more abstract forms to create a new layer or dimension of realism. The placement of smaller materials help the eye flow across the overall form, with accents such as resin seeming to flow like rivers, clusters of beads stretching outward, and various carvings of shapes pointing in certain directions, organizing together in patterns and recognizable symbols. This essentially lets the viewer find themselves lost in the artwork, finding intentional, or unintentional meanings in the art whilst still being able to return in larger composition. A diversity of materials allows the art to portray a variety of aesthetics ranging from something raw and organic, like the look of plants, stone, or burnt wood, to something entirely artificial, with the use of industrial parts, polished metal, glass, fluorescent paints, digital fabrication, and computer animation. This allows the art to tell a multitude of narratives. In many cases, it is a physical representation of our evolution from the primitive to the modern. Furthermore, the synthesis of these materials in unconventional ways allows for environments to form that only exist in imaginative space.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.